Genotype-environment interaction and yield stability in advanced lines of ají topito (Capsicum chinense) - Muñoz-Falcon, Julio Ernesto (2024)
Introduction. Sweet bell pepper (Capsicum chinense Jacq., sinense Murray) is a traditional crop of the Caribbean region of Colombia, which occupies the third place among the vegetables planted in this area this area of the country. Objective. To evaluate the genotype-environment interaction and yield stability in nine advanced lines of topito type sweet pepper obtained within the vegetable breeding program of the Colombian Agricultural Research Corporation (AGROSAVIA). Materials and methods. In the year 2020, four agronomic evaluation trials were established in the localities of San Pelayo, Córdoba; Sincelejo, Sucre; Suan, Atlántico, and Zona Bananera, Magdalena, all located in the Caribbean region of Colombia. For the experiments, a design of complete blocks at random with four repetitions was carried out. As variables for the answer, the yield, the number of fruits per plant, the fresh weight of the fruit and the length of the fruit are considered. Phenotypic yield stability analyses were carried out using the methods proposed by Eberhart and Russell, and Lin and Binns. Results. The results demonstrated the existence of a significant genotype-environment interaction for variables associated with fruit yield. Through the analysis of the productive behavior of materials in different environments, it was possible to identify the advanced lines L61 and L7 as outstanding genotypes with statistically superior yields (p ≤ 0.05) in the regional test used and with fruit characteristics according to the requirements of the regional fresh consumption market. Conclusions. The L61 and L7 genotypes showed the best adaptation to the different environments evaluated and the greatest productive potential. The Banana Zone environment achieved the highest yields, with 59.11 t ha-1 for L61 and 55.05 t ha-1 for L7.